Achieving Supply Chain Resilience: The Role of Digital Transformation and Supply Chain Process Integration in Market Uncertainty - Handijaya, Elizabeth Maeko Cyrilla; Kodrat, David Sukardi; Sutrisno, Timotius F.C.W. (Universitas Brawijaya, Indonesia, 2024)
In Indonesia's logistics sector, the challenges exacerbated by the COVID-19 pandemic highlight the urgent need for a supply chain. While digital transformation offers a promising solution, its impact remains to be determined. To close this gap, this paper examines the intricate connection between supply chain resilience and digital transformation in Indonesia's logistics sector. Understanding these dynamics is critical to strengthening supply chains and effectively dealing with market uncertainty. Research data from 180 logistics companies in Java and Bali and Analysis using the SEM-PLS (Structural Equation Modeling Partial Least Squares) model was done. The results show that digital transformation significantly impacts supply chain process integration and improves supply chain resilience. The presence of market uncertainty then modifies the link between supply chain resilience and supply chain process integration. However, market ambiguity doesn't mitigate the connection between supply chain process integration and the robustness of the supply chain.